Muskism : a guide for the perplexed - Slobodian, Quinn, 1978-; Tarnoff, Ben (Harper, 2026)
A pyrotechnic examination of Elon Musk as a symptom and avatar of our postliberal age. Everyone's got an Elon take. He's a messiah. A menace; a genius; a clown. The verdicts differ, but they share one theme: they treat him as an individual. Muskism argues otherwise. Elon Musk isn't a glitch in the system--he is the system. His worldview promises sovereignty through technology: plug in, power up, and become self-reliant. But the more you connect, the more he owns you. If Fordism defined the capitalism of the twentieth century, Muskism may define the twenty-first. Fordism helped build the welfare state. Musk undoes it. He thrives on dependence while preaching freedom. His cars run on subsidies; his satellites run the battlefield; his social networks train the AI that trains us. Muskism sells itself as the future but entrenches age-old hierarchies. It offers autonomy for some and exclusion for others. It's pro-natalist but anti-immigrant, futurist but reactionary. It speaks of humanity but warns against empathy. Quinn Slobodian and Ben Tarnoff cut through the hype and the hate to reveal what Musk really represents: a new political economy, where to be "free" means to serve a Technoking. Muskism isn't about the man. It's about the machine that made him--and the world he's making next.